One-Pot Synthesis of Hydrophilic and Hydrophobic N-Doped Graphene Quantum Dots via Exfoliating and Disintegrating Graphite Flakes - Kuo, Na-Jung; Chen, Yu-Syuan; Wu, Chien-Wei; Huang, Chun-Yuan; Chan, Yang-Hsiang; Chen, I-Wen Peter (Scientific reports, 2016)
Graphene quantum dots (GQDs) have drawn tremendous attention on account of their numerous alluring properties and a wide range of application potentials. Here, we report that hydrophilic and hydrophobic N-doped GQDs can be prepared via exfoliating and disintegrating graphite flakes. Various spectroscopic characterizations including TEM, AFM, FTIR, PL, XPS and Raman spectroscopy demonstrated that the hydrophilic N-doped GQDs (IN-GQDs) and the hydrophobic N-doped GQDs (ON-GQDs) are mono-layered and multi-layered, respectively. In terms of practical aspects, the supercapacitor of an ON-GQDs/SWCNTs composite paper electrode was fabricated and exhibited an areal capacitance of 114 mF/cm 2 , which is more than 250% higher than the best reported value to date for a GQDs/carbon nanotube hybrid composite. For IN-GQDs applications, bio-memristor devices of IN-GQDs-albumen combination exhibited on/off current ratios in excess of 10 4 accompanied by stable switching endurance of over 250 cycles. The resistance stability of the high resistance state and the low resistance state could be maintained for over 10 4 s. Moreover, the IN-GQDs exhibited a superior quantum yield (34%), excellent stability of cellular imaging and no cytotoxicity. Hence, the solution-based method for synchronized production of IN-GQDs and ON-GQDs is a facile and processable route that will bring GQDs-based electronics and composites closer to actualization.